Membentuk Softskill Mahasiswa Akuntansi melalui Effective Team Building dalam Ruang Kelas: Sebuah Aplikasi Mcgrath’s Model - Se Tin (Jurnal Akuntansi dan Bisnis, 2007)
This paper aims to provide guidelines for accounting educators who wish to promote team-building competencies within group projects. This paper also give the application how to build effective team in class usage of McGrath’s model and guidance that develops by Bryant and Albring (2006). The number of 50 accounting students in research methodology class of Maranatha Christian University participated in this application. The project is make a mini research. The results show that the students have a significant differences in their attitudes and behavior from the experience in the new team.